2020
DOI: 10.30762/q.v4i2.2452
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Implementasi Fatwa Majelis Ulama Indonesia Nomor 23 Tahun 2020 Sebagai Upaya Pemulihan Ekonomi Oleh Lembaga Amil Zakat (Mui Fatwa Implementation Business Number 23 Year 2020 in Economic Recovery by Amil Zakat Institution)

Abstract: Penelitian ini bertujuan untuk menganalisa adakah implementasi dari Lembaga Amil Zakat dalam hal ini adalah Yayasan Yatim Mandiri cabang Kediri dalam menyikapi adanya Fatwa MUI Nomor 23 Tahun 2020 tentang pemanfaatan harta zakat, infak, dan shadaqah untuk penanggulangan wabah covid-19 dan dampaknya terutama dalam bidang ekonomi yang berdampak pada kondisi kesejahteraan masyarakat. Teori yang digunakan dalam penelitian ini adalah konsep kesejahteraan Imam Ghazali dan juga Fatwa MUI Nomor 23 tahun 2020. Sedangka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the midst of a Covid-19 pandemic, Indonesia's economy saw a decline/weakening due to limits placed on communal activities to prevent the spread of the Covid-19 virus, which might have catastrophic effects for the people's economy, which is impacted usually by the existence of this new phenomenon (Mutafarida & Fahmi, 2020). In the first quarter of 2020, as a result of the Covid-19 pandemic, which had been ongoing since the start of the year, the Indonesian economy contracted., From this, it can be observed that Indonesia's economic growth in the most recent quarter was only 2.97 percent, a significantly smaller fall than the previous quarter's rise of 4.97 percent (Mutafarida & Fahmi, 2020).…”
Section: Results and Discussion The Role Of Baznas Through The Mustah...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the midst of a Covid-19 pandemic, Indonesia's economy saw a decline/weakening due to limits placed on communal activities to prevent the spread of the Covid-19 virus, which might have catastrophic effects for the people's economy, which is impacted usually by the existence of this new phenomenon (Mutafarida & Fahmi, 2020). In the first quarter of 2020, as a result of the Covid-19 pandemic, which had been ongoing since the start of the year, the Indonesian economy contracted., From this, it can be observed that Indonesia's economic growth in the most recent quarter was only 2.97 percent, a significantly smaller fall than the previous quarter's rise of 4.97 percent (Mutafarida & Fahmi, 2020).…”
Section: Results and Discussion The Role Of Baznas Through The Mustah...mentioning
confidence: 99%
“…63 billion And in 2021 alone, infaq and charity monies of Rp 53.2 billion will be disbursed (Achmad, 2021). Due to the recession in the form of a weakening Indonesian economy as a result of restrictions on community activities to avoid the spread of the Covid-19 virus, the amount of infaq and sadaqah funds for 2020 and 2021 has decreased (Mutafarida & Fahmi, 2020). And not only does it affect the economy of low-income individuals, but also the economy of the wealthy, through loss-making or bankrupt businesses, lower business turnover, etc (Amanda et al, 2021).…”
mentioning
confidence: 99%
“…So far quite a lot of research has been conducted with a focus on highlighting fatwas issued by the MUI (Alkawy, 2020;Mutafarida & Fahmi, 2020;Saadi et al, 2021;Simal, 2019;Tamam, 2021;Wijaya et al al., 2021;Yusefri, 2022) , although there are different views in conducting the study of the MUI fatwa. The large number of studies conducted show the importance of the fawa issued by the MUI to explore its aspects and objects, where the tools used by the government, apart from being in the form of statutory law (Hamid, 2021) , fatwa are also a supporting tool for the political products produced.…”
Section: Political Economy and Fatwa Research Studiesmentioning
confidence: 99%